The declining availability of wild mussel seed for aquaculture in a coastal upwelling system - Padin, Xosé A.; Babarro, José M. F.; Otero, Pablo; Gilcoto, Miguel; Rellán, Trinidad; Suárez, Lino; Velo, Anton; Peteiro, Laura G. (Frontiers in Marine Science, 2024)
A general decline in foundation species at the rocky intertidal has been observed during the last decades all around the world and primarily related to climate change. In agreement with that trend, the mussel aquaculture sector in Galicia (NW Spain), the main production area in Europe, has warned over the last years about a decline in the availability of wild mussel seed from the rocky coast. Here we compile for the first time, mussel seed collection reports by mussel farmers in Galicia for the period 2006–2021. We employed that dataset as a proxy of mussel recruitment evolution in the rocky shore for the last 16 years. Temporal analysis of our data confirmed the reported decline (-148 t yr-1), particularly pronounced from 2012 onwards. The data base also allowed us to analyze inter-annual variability according to both, climatic variations and management scenarios. Since cultivated mussels conform a meta-population with wild mussels from the rocky shore, alterations on the market preferences towards smaller individuals at harvest, could also contribute to a reduction in reproductive output. Our results show a decrease in life-time egg production under certain scenarios. Nonetheless, coastal upwelling seems to be the largest factor conditioning recruitment abundance, explaining as much as 60% of the variability observed. Decline on recruitment abundance was highly modulated by the observed increment in frequency of intense upwelling events, exceeding 500 m3 km-1 s-1 between July and November. Meridional winds also determined the spatial recruitment patterns, pointing to the large role of wind forcing on mussel larval dispersal. Our results highlights how alterations on upwelling regimes related to climate change can interact with mussel population dynamics and also condition aquaculture sustainability and food security.